x+13=-2/3

Simple and best practice solution for x+13=-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+13=-2/3 equation:



x+13=-2/3
We move all terms to the left:
x+13-(-2/3)=0
We get rid of parentheses
x+13+2/3=0
We multiply all the terms by the denominator
x*3+2+13*3=0
We add all the numbers together, and all the variables
x*3+41=0
Wy multiply elements
3x+41=0
We move all terms containing x to the left, all other terms to the right
3x=-41
x=-41/3
x=-13+2/3

See similar equations:

| (x+8)=63 | | 0.08x+0.06(x+9)=1/4 | | 12=q2+ 9 | | w/25=9 | | 8n–5=4–2n | | 10x=126000 | | 9x=3(2x)-5) | | 52=2w+1+w | | 1(a+3)=a+3 | | 9x=3(2x)-5 | | 2t(0)=0 | | 2/49=x/7 | | (9+x)=70 | | 100/150=6/n | | 13/5x-14=1/2(3x-8 | | 5=n50 | | 67+k=97 | | n– 8 = 23 | | 8.25d+65=683.75 | | 3(x-1)+5x=40 | | F(-2a)=(-2a)^3 | | 7/14=7x | | 0.5x-7=-24 | | -1/2u=-13/30 | | 2(b+6)=14 | | (5x2+x−10)−(5x2+8x−10)=10 | | -w+90=246 | | 3(6y)+5y=0 | | 115=213-v | | 17=r/3 | | -9-y=28 | | 5x-3=49-7 |

Equations solver categories